Pratiques funéraires dans l’Arabie antique : la nécropole de Thaj - Marie Laguardia; Olivia Munoz; Jérôme Rohmer; Patrice Courtaud (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In north-eastern Arabia, a new phase of settlement expansion began in the 4th-3rd centuries BCE, as the region became a crossroads for trade between southern Arabia, the Indian Ocean, Mesopotamia and the Mediterranean. A remarkable aspect of this "renaissance" was the development of vast tumulus necropolises, which seems to have revived a regional building tradition dating back to the 3rd millennium BCE. The largest settlement founded at this time, Thaj, is located in the eastern province of present-day Saudi Arabia and was occupied until shortly before the advent of Islam. The site consists of a walled city covering 40 ha, a suburban area and a large necropolis with at least 1000 tombs. In 2017, a new archaeological investigation of this necropolis was launched, as part of the Saudi-French Thaj Archaeological Project. The survey and the excavations carried out so far, together with the findings from previous fieldwork by the Saudi Department of Antiquities, have made it possible to establish a typology of the funerary monuments, characterize their construction techniques and better understand the spatial organization of the necropolis. The excavations have also revealed the diversity of the graves, which differ in their architecture and the funerary treatments applied to the dead. Finally, a series of radiocarbon dates obtained for the excavated graves shows that some of the funerary monuments were used and maintained for several centuries, while the associated material provides evidence for funerary rituals carried out either at the time of the funeral or during later commemorative ceremonies.